Optimization Design of the Three Pinions Synchronous Drive System of Shield Cutter - Wang Sixia; Chen Xin (Jixie chuandong)
The mathematical model is established with the minimum volume of the three pinions synchronous drive system of shield cutter,and the model is solved by the genetic algorithm. Then the load sharing characteristic of different installation arrangement of the three pinions synchronous drive system is analyzed. The results show that the design efficiency and accuracy can be improved by the genetic algorithm. The optimization results met the requirements of reducing weight and saving energy. The load sharing characteristic of system is good in type of 30°-150°-270°. The study can provide theoretical basis for the design and manufacture of the multiple pinions parallel drive system.